(9x-8)=(8-9x)

Simple and best practice solution for (9x-8)=(8-9x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (9x-8)=(8-9x) equation:


Simplifying
(9x + -8) = (8 + -9x)

Reorder the terms:
(-8 + 9x) = (8 + -9x)

Remove parenthesis around (-8 + 9x)
-8 + 9x = (8 + -9x)

Remove parenthesis around (8 + -9x)
-8 + 9x = 8 + -9x

Solving
-8 + 9x = 8 + -9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9x' to each side of the equation.
-8 + 9x + 9x = 8 + -9x + 9x

Combine like terms: 9x + 9x = 18x
-8 + 18x = 8 + -9x + 9x

Combine like terms: -9x + 9x = 0
-8 + 18x = 8 + 0
-8 + 18x = 8

Add '8' to each side of the equation.
-8 + 8 + 18x = 8 + 8

Combine like terms: -8 + 8 = 0
0 + 18x = 8 + 8
18x = 8 + 8

Combine like terms: 8 + 8 = 16
18x = 16

Divide each side by '18'.
x = 0.8888888889

Simplifying
x = 0.8888888889

See similar equations:

| (3n)+4=18+n | | 8+2b=280 | | P-(-40)=34 | | -5t^2+60t+74=0 | | 27-24x-4x+24x+32=11 | | G(x)=x^2+8x+17 | | 85=10-2.5v | | 3y=4yx-1x | | 3(x+1)+2(x+4)= | | x+3.5x+20=56 | | 9x-6x=8 | | 3(4y+2)+7y= | | 8x^2-2x+2=0 | | 6(u-9)-1=-5(-3u+8)-3u | | 5+(9+18-3)-3= | | 7(m+5)=22 | | 8-n=34 | | 7nsquared+7=12n | | 2(4x+3)+6= | | -56=88-9x | | 29-7x=28x-28 | | 9+14x+5x=180 | | 7-2f=1.98 | | 10-2y+4x=0 | | -7[4+7(-5+7)]+16= | | 50+3b=134 | | 3(1)=3 | | 7x+6=2z+2 | | 12x-13=-6x | | 6a-9-8a+5a= | | 5x+200=3x-300 | | -23n+13n+47-5n=-28 |

Equations solver categories